High diversity mixed plantations in Brazil: Eucalyptus intercropped with native tree species - Amazonas, Nino Tavares (2018)
The high cost of restoring tropical forests is one of the greatest obstacle to achieving large-scale restoration. To overcome this barrier, we developed and implemented mixed plantations intercropping Eucalyptus with a high diversity of native tree species. The aim was to create favorable conditions for the regeneration of native species while simultaneously obtaining economic return from the exploitation of Eucalyptus as a commercial pioneer species. The use of Eucalyptus in this system is temporary and it shall be replaced by additional native species after it is harvested. In this research, we covered the main aspects and approaches of the effects of competition on tree growth using data from our restoration experiments. The objective of this research was to test the ecological viability of plantations that temporarily mix Eucalyptus spp. and a high diversity of native tree species during the initial phases of forest restoration as a strategy to offset implementation and maintenance costs. This alternative is investigated with a focus on the consequences of ecological interactions on tree survival and growth in three experiments implemented in the Atlantic Forest of Northeastern and Southeastern Brazil. We compared stands of native trees intercropped with Eucalyptus, traditional restoration plantations, and Eucalyptus monocultures. The thesis is structured in three main parts in which we focus in how the mixtures function compared to restoration plantations and Eucalyptus monocultures. We used forest inventories to understand the effects of competition and assessed ecophysiological parameters to provide insights about the mechanisms that affect tree growth when trees compete for water, light and nutrients. In the first part of the study, we showed that mixed plantations effectively combined high wood yield and tree diversity; that Eucalyptus grew larger in mixtures with native species than in monocultures; that native tree species grew less in mixtures with Eucalyptus; and that the mixing effect was stronger for fast- and intermediate-growing native species. In the second part, we found that mixtures consumed less water than monocultures; that Eucalyptus reduced the hydraulic performance of a fast-growing native species; and that tree growth was influenced by changes in the ecophysiology of water use. In the last part, we showed that a high diversity of nitrogen-fixing native trees facilitated Eucalyptus growth; that Eucalyptus had ~30% higher wood N concentration in mixtures; that native trees growth was not limited by nutrient competition with Eucalyptus; that Eucalyptus may benefit from increased light availability in mixed plantations; and that native species plots intercepted more sunlight than mixtures or Eucalyptus stands. This research has a strong interface between restoration science and practice, and contributed to the development of new ways to restore the tropical forests by allying restoration and production under the ecological and economic perspectives. Our findings indicate how to advance into the future, starting from the current state of art towards forest restoration systems that minimize competition and maximize growth, as an emergent promising alternative to finance tropical forest restoration and overcome the economic barrier that still holds large-scale restoration. This research may be used as a basis to continue adapting silviculture for different regions and forest ecosystems. Looking further into the future, these mixtures may also represent the starting point of a new silvicultural model that brings together production and conservation. The information available may be used by scientists, decision-makers, planners and restorationists to advance in the science and practice of restoration and silviculture in the tropics.